Los mamíferos de México en las colecciones científicas de Norteamérica - Lorenzo, Consuelo; Álvarez-Castañeda, Sergio Ticul; Arellano, Elizabeth; Arroyo-Cabrales, Joaquín; Bolaños, Jorge; Briones-Salas, Miguel; Cervantes, Fernando A.; Chablé-Santos, Juan; Corral, Leonardo; Cortés, Malinalli; et al. (THERYA, 2012)
Updated information on the geographic and taxonomic representativeness of mammal specimens deposited in 28 Mexican mammal collections, the Mammal Networked Information System (MaNIS), and the Unidad de Informática para la Biodiversidad (UNIBIO) data bases were compiled in order to analyze and compare the overall current status of the specimens of Mexican mammals deposited in collections in North America. A total of 421,466 specimens deposited in 120 collections were documented, of which 233,116 were deposited in collections in the United States of America and Canada, and 188,350 in collections in Mexico. The collections with the greatest number of specimens from Mexico are the Colección Nacional de Mamíferos (CNMA 46,000), the University of Kansas (KU 44,301), and the Escuela Nacional de Ciencias Biológicas (ENCB 43,985). In Mexican collections, the states of northern Mexico are improperly represented in number of specimens (< 3,000), whereas in foreign collections, the states of central Mexico are poorly represented. The Mexican states better represented by number of specimens (> 10,000) are Baja California Sur, Chiapas, Oaxaca, Puebla and Veracruz. The orders better represented in terms of number of specimens are Rodentia and Chiroptera (234,978 and 120,956, respectively). The Mexican states with the smallest area have the greatest density of specimens collected (specimens/km2), such as Distrito Federal (3.2), Tlaxcala (1.4), Colima (1.06), and Morelos (0.9). The aim of this analysis is to provide a baseline to establish appropriate strategies to complete the national inventory of Mexican mammals and to ensure that this natural heritage is fully represented within Mexican collections.